Comparative morphology and functional significance of mechanical and sensory structures in the upper digestive tract of the ostrich (Struthio camelus) and emu (Dromaius novaehollandiae) - Soley, John Thomson (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.